2018
DOI: 10.25252/se/18/51390
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and erosion as affected by tillage system and polyacrylamide in two sandy loam soils differing in silt and clay contents in semi-arid regions

Abstract: This study aims to investigate the effect of three tillage practices and the effect of polyacrylamide application rate on surface runoff and erosion of sandy loam soils differing in silt and clay contents. Field experiments in splitsplit plot with four replications were carried out in two different locations; location A that consists of 25.2% silt plus clay and location B which consists of 38.5% silt plus clay. Three tillage practices were investigated; no-tillage (NT), mouldboard ploughing with rotor tiller (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The runoff and soil loss were reduced for all slope shapes after applying PAM on the slope surface (Figures 3 and 4). For the impact of runoff, Yu et al (2003) and Abu-Hamdeh et al (2018) showed that PAM improves soil structure and inhibits the soil crust, thereby preventing the reduction of soil infiltration capacity during rainfall. After PAM dissolves, the negatively charged PAM molecules are adsorbed together with the soil particles by cations (Ca 2+ ), thereby enhancing the stability of the soil aggregates (Inbar et al, 2015;Lentz & Bjorneberg, 2003).…”
Section: Impact Of Pammentioning
confidence: 99%
See 1 more Smart Citation
“…The runoff and soil loss were reduced for all slope shapes after applying PAM on the slope surface (Figures 3 and 4). For the impact of runoff, Yu et al (2003) and Abu-Hamdeh et al (2018) showed that PAM improves soil structure and inhibits the soil crust, thereby preventing the reduction of soil infiltration capacity during rainfall. After PAM dissolves, the negatively charged PAM molecules are adsorbed together with the soil particles by cations (Ca 2+ ), thereby enhancing the stability of the soil aggregates (Inbar et al, 2015;Lentz & Bjorneberg, 2003).…”
Section: Impact Of Pammentioning
confidence: 99%
“…Moreover, soil erosion and nutrient loss are also related to soil properties and soil and water conservation measures (Ramos et al, 2015). Polyacrylamide (PAM) is widely used in soil and water conservation as a soil improver (Abrol et al, 2013; Abu‐Hamdeh et al, 2018; Yoon et al, 2011). PAM is a highly segmented organic compound that has strong adhesion after being dissolved (Ao et al, 2018; Yu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%